Control characteristics of an automatic matching control system for in vivo EPR spectroscopy - Hirata, Hiroshi; Yamaguchi, Yasunori; Takahashi, Tatsuhisa; Luo, Zhi-Wei (Magnetic resonance in medicine, 2003)
A method for estimating the characteristics of an automatic matching control (AMC) system for in vivo electron paramagnetic resonance (EPR) spectroscopy is described. AMC is also known as automatic coupling control (ACC) and is used to compensate for perturbation due to movement of the subject animal. The open‐loop function of the AMC system is derived and the characteristics (gain, phase margin, steady‐state error, system bandwidth, and disturbance rejection) of the system are examined. The proposed method is supported by experimental findings. The frequency response of perturbation due to the movement of an anesthetized rat was measured with a 1.1‐GHz continuous‐wave EPR spectrometer. Disturbance rejection with the AMC system was also considered for respiratory motion and the heartbeat of the anesthetized rat, and these perturbations were reduced by about 40 dB in the power spectrum of the output of the diode detector in the spectrometer. Magn Reson Med 50:223–227, 2003. © 2003 Wiley‐Liss, Inc.